Yogyakarta Tourism Promotion using User-Generated-Content Feature - Amalia, Ayu; Sudiwijaya, Erwan (Komunikator, 2020)
The interactivity feature on social media raises crucial aspects in the era of user generated content, where internet users act as producers and consumers of media content. Tourism as an important sector of the Special Region of Yogyakarta. This study described the dynamics of Instagram account user communication in conducting recommendations on natural tourism spots in Yogyakarta, researchers conducted an analysis based on uploaded content typology, corelated with user generated content, also described the process of data analysis using social media analytics tools obtaining data based on specific keywords or trending topics, such as hashtags usage from Instagram account with tourism photography themed, known as @explorejogja. As resulted, there are recommendation type of engagement, followed by invitation to visits tourism destination, and review-like type of engagement, all derived and formulated from @explorejogja’s followers. Instagram, as a social media based on visual sharing feature, appropriate utilized as a media to promote tourism potential, especially in Yogyakarta, given the tendency of its engagement is organic, to motivate Instagram users to visit tourism potentials, as is conducted @explorejogja for tourism potential located in the Yogyakarta region.